Citra Distorsi Kebijakan Pengelolaan Sumber Daya Air di Daerah Irigasi Jengkelok - Nurzaman, Usman; Faozanudin, Muslih; Nuraini, Hikmah (IAI Nasional Laa Roiba Bogor, 2025)
The Policy of Water Resource Management in water distribution to agricultural land faces dysfunctional channels, which should aim for farmers welfare, but this is not the case. This research focuses on the management of the BL4 Left Tertiary Channel in meeting farmers water needs, which is disrupted by illegal street vendor structures built over the channel for more than 30 years. The implementation of policies regarding the BL4 Left Tertiary Channel in the Jengkelok Irrigation Area is influenced by various factors, including the occupation of channel space by street vendors. This study employs a qualitative approach through field observations and relevant literature reviews. The findings reveal that residents suffer significant losses due to street vendors structures obstructing the channel. The management of the BL4 Left Tertiary Channel fails to align with the intended policy goals and its implementation in the field, resulting in the tertiary channel functioning abnormally. These findings provide a critical perspective on how policy distortions can hinder the optimization of water resources, emphasizing the importance of strengthening collaboration between the government, community, and other stakeholders.